Peningkatan Daya Saing UMKM Desa Lemah Abang Melalui Pembangunan Dan Manajemen Website - Gifthera Dwilestari; Edi Tohidi; Raena Agustin Laeliyah; Anita Nur Kirana; Hilya Ashfia Nabila (AMMA : Jurnal Pengabdian Masyarakat, 2022)
This community service is an initiative that aims to overcome the challenges faced by Micro, Small and Medium Enterprises (MSMEs) in Lemahabang Village in facing the digital era[1]. In the midst of the rapid development of information technology, websites have become a crucial tool for MSMEs in developing their business. However, many MSMEs in rural areas such as Lemahabang Village still face obstacles in understanding and managing their websites. In this situation analysis, we will explain the location of the partners and the cases that occurred, the social and cultural conditions of Lemahabang Village, the special problems faced by MSMEs there, the methods or approaches used in the service, and the implications of the results of the service for the community. The results of the activity "Increasing the Competitiveness of MSMEs in Lemah Abang Village through Website Development and Management" have had a very positive impact on MSMEs in the village. The implementation of the website has succeeded in expanding the market reach of MSMEs in Lemah Abang Village. There was a significant increase in the number of visits to the website, which indicates greater interest from consumers outside the region and there was a marked increase in the sales volume of MSME products after the implementation of the website. This reflects the effectiveness of digital platforms in supporting business transactions.